Epistemology of the paintings contained qur'ānic verses / Sallehuddin Mohamed, Mumtaz Mokhtar and Abd. Rauf Hassan - Mohamed, Sallehuddin; Mokhtar, Mumtaz; Hassan, Abd. Rauf (Universiti Teknologi MARA, 2020)
The possession of the Art and Design knowledge, Islamic knowledge, Arabic scripts and memorised Qur'ānic verses, enabled the Muslims artists to produce artworks contained Qur'ānic verses. They believed that there is goodness in the painting contained the Qur'ānic verses. The Qur'ānic verses are from the Holy Qur'ān, and it is the final revelation. The not yet Muslim's intellectuals who are searching for the true religion, reverted to Islam after study the Qur'an and found that the contents of the Qur'ān are the true revelation. The Qur'ān is "un-imitable" in its unparalleled language and literary style, its contents, and powerful spiritual impact. The Muslim artists and the Muslim art appreciators or viewers who recite the verses will receive good deeds. The good deeds (rewards) are the true gift and the Qur'ān speaks the truth. The Qur'ānic verses are the subject in the paintings and the main discourse towards the philosophy. The beauty and the contents of the paintings with the Qur'ānic verse or verses have signs and messages that speak the truth for those who believed the unseen (al-ghaib). Therefore, the epistemology of the contemporary Islamic painting contained the Qur'ānic verses visualised the goodness, good deeds, truth and beauty.